Efficiency of cares over toothbrush storage to prevent contamination - Santos, Patrícia Aleixo dos; Bozelli, Aline Maria; Cardinalli, Érika Tieko Kaibara; Bernardi, Adilson César Abreu; Campos, Juliana Alvares Duarte Bonini [UNESP]; Oliveira, Ana Luísa Botta Martins de [UNESP] (My University, 2013)
This study evaluated the efficiency of a toothbrush holder to prevent contamination of toothbrushes used by preschool children. For that, the sample was composed by children 6 years old, enrolled in an educational and recreational center in Araraquara/SP, and divided into 3 groups: G1: same continuing routine storage toothbrushes, G2: children received only a new toothbrush holder for storage; G3: they received new toothbrushes holder for storage and solution of chlorhexidine digluconate to 0.12% to dabble in the toothbrush after use. After brushing their teeth, toothbrushes were collected for microbiological analysis. The data were analyzed using the distribution of frequencies. It was observed that, in general, higher prevalence of the microorganism in the toothbrushes was Streptococcus viridans (58.97%), followed by Estafilococcus (35.90%), the bacillus of air (28.21%) and Neisseria mucosa (5.13%). Evaluating frequency, it was noted that the contamination presented by Streptococcus is higher in G1 when compared to G2 and G3, while for Estafilococcus, the presence was more significant in G3. Thus, it was concluded that the use of new toothbrushes holder able to avoid direct contact between brushes and allow drying without smothering could be an excellent alternative to educational institutions that require the storage group.
Keywords: Toothbrushing; Contamination; Oral hygiene